Effects of Different Combinations of Cow Dung and Jeewamirtha Application on Growth and Yield of Vigna Unguiculata L. - Nowe, M. F.; Sutharsan, S.; Srikrishnah, S.; Rifnas, L. M. (Asian Journal of Science and Applied Technology, 2023)
Cowpea is one of the important vegetable crop in Sri Lanka as well as many other countries. Chemical fertilizer application of cowpea production leads to hazardous effect of agro ecological system. In this regard, an experiment was conducted to study the effects of different combinations of Cow dung and Jeewamirtha on growth and yield of Vigna unguiculata. The experiment was laid out in Completely Randomized Design with six treatments and ten replications. The treatments are T1 (100% Jeewamirtha), T2 (75% Jeewamirtha + 25% Cow dung ), T3 (50% Jeewamirtha + 50% Cow dung), T4 (25% Jeewamirtha + 75% Cow dung), T5 (100% Cow dung), T6 (control ). The Experimental results showed that, T2 treatment, the plants treated with 75% Jeewamirtha and 25% Cow dung significantly increased the Fresh and Dry weight of shoot (38.90 %, 47.2 %), Days for 50 % flowering (23..6%),Number of pods per plant (44.5 %), 100 seeds (34.0 %) and Total yield per hectare (50.% ) in comparison to plants treated with Control treatment (T6). Therefore, the 75% Jeewamirtha and 25% Cow dung fertilizer could be recommended for the cultivation of Vigna unguiculata in order to enhance the growth and yield which is environmentally friendly for sustainable Agriculture.